الابتكار المالي في التمويل و أهميته في تحقيق كفاءة و فعالية أداء البنوك الإسلامية - بريش، عبدالقادر; خلدون، زينب Khaldoun, Zeinab (جامعة حسيبة بن على الشلف - كلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير, 2016)
Today, the financing in accordance with Islamic shariah gains a great importance because of its capacity to build bridges of confidence between the Islamic bank and its customers, but this confidence first requires the initiative of innovating legal and diversified fund products in order to meet the aspirations of various social groups and respond to the required purpose which consists of achieving efficiency and effectiveness of Islamic bank , the achievement of this equation exceeds the Islamic banking system limits and guarantees the prosperity and development of the Islamic economy and even the non-Muslim majority communities.
إن التمويل الموافق للشريعة الإسلامية يكتسب اليوم أهمية كبيرة نظرا لقدرته علي مد جسور الثقة بين البنك الإسلامي وعملائه، لكن بناء هذه الثقة يتطلب أولا المبادرة إلى ابتكار منتجات تمويل شرعية أمنة ومتنوعة تلبي تطلعات مختلف الفئات الاجتماعية وتفي بالغرض المطلوب وهو تحقيق كفاءة وفعالية العمل الذي يقدمه البنك الإسلامي، إذ أن تحقيق هذه المعادلة يتعدى حدود العمل المصرفي الإسلامي ليضمن للاقتصاد الإسلامي الازدهار والنمو حتى في المجتمعات ذات الغالبية غير المسلمة.
Keywords: البنوك الإسلامية -- السياسة المالية -- الابتكار المالي -- الصيرفة الإسلامية -- الصكوك الإسلامية